2017
DOI: 10.1590/s0100-204x2017000900015
|View full text |Cite
|
Sign up to set email alerts
|

Botrytis bunch rot on 'Sauvignon Blanc' grapevine on the Y-trellis and vertical shoot-positioned training systems

Abstract: -The objective of this work was to evaluate the effect of the Y-trellis (YT) and vertical shootpositioned (VSP) training systems on the incidence and severity of Botrytis cinerea, on cluster compactness, and total polyphenol (TP) contents of 'Sauvignon Blanc' grapevine (Vitis vinifera) in the municipality of São Joaquim, in the state of Santa Catarina, Brazil. Field trials were carried out in a randomized complete block design during the 2013/2014 and 2014/2015 crop seasons, with assessments performed at harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…In a previous study evaluating botrytis bunch rot in two training systems (VSP and Y) with 'Sauvignon Blanc', Bem et al (2017) observed higher compactness in clusters produced in Y-trellis, which also resulted in higher incidence and severity of botrytis bunch rot. The Y-trellis tends to reduce vine vigor, leading to a better balance between vegetative growth and production (Reynolds and Vanden Heuvel, 2009); however, due to the higher nutrient flow to the berries, there is also an increase in cluster compactness (Hernandes et al, 2013).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In a previous study evaluating botrytis bunch rot in two training systems (VSP and Y) with 'Sauvignon Blanc', Bem et al (2017) observed higher compactness in clusters produced in Y-trellis, which also resulted in higher incidence and severity of botrytis bunch rot. The Y-trellis tends to reduce vine vigor, leading to a better balance between vegetative growth and production (Reynolds and Vanden Heuvel, 2009); however, due to the higher nutrient flow to the berries, there is also an increase in cluster compactness (Hernandes et al, 2013).…”
Section: Resultsmentioning
confidence: 84%
“…The cluster compactness index is considered an important factor to assess grape quality (Tello and Ibáñez, 2014). This condition can make plants more susceptible to fungal diseases, especially Botrytis cinerea (Evers et al, 2010;Bem et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De acordo com Molitor et al (2012), Molitor et al (2014) e Bem et al (2017), medidas culturais que resultam em maior exposição solar e ventilação na região dos cachos, como o manejo da desfolha, são ferramentas eficientes nas estratégias de controle da B. cinerea nos cachos da videira. E em plantas submetidas a elevadas cargas de gemas planta -1 , deve-se realizar essas medidas culturais, como a desfolha no estádio baga chumbinho, proporcionando maio eficiência no controle da doença (Wurz et al, 2017b;Wurz et al, 2020b).…”
Section: Carga Deunclassified